Sex differences in the weight response to GLP-1RA in people with type 2 diabetes. A long-term longitudinal real-world study - Marella Marassi; Andrea Cignarella; Giuseppina T. Russo; Laura Nollino; Marco Strazzabosco; Paolo Marzullo; Frida Leonetti; Angelo Avogaro; Agostino Consoli; Gian Paolo Fadini (Pharmacological Research, 2025)
Sex differences may influence pathophysiology, treatment response, and outcomes of type 2 diabetes (T2D). We assessed whether sex affected clinical response to GLP-1 receptor agonists (GLP-1RA) in a large real-world cohort. Thus, we conducted a multicentre, retrospective, longitudinal study of 7847 individuals with T2D initiating GLP-1RA therapy across 18 Italian diabetes centres. Participants were stratified by self-reported sex. The primary outcome was change in body weight over time; secondary outcomes included changes in HbA1c, renal function, and lipid profile. Analyses were performed using a mixed model for repeated measures, adjusting for baseline imbalances.Participants were 60 % male, with similar age, diabetes duration, and HbA1c (mean 8.0 %). Females had higher BMI but fewer micro- and macrovascular complications. Over a median 4-year follow-up, females experienced significantly greater weight reduction than males (adjusted mean difference: −1.1 kg; p < 0.001), with more females achieving a weight loss of ≥ 5 % (66.5 % vs. 58.0 %, p < 0.001) or ≥ 10 % (40.0 % vs 30.7 %, p < 0.001). This sex difference in weight loss remained unchanged after progressive adjustment for variables that differed between males and females, across GLP-1RA molecules, and after accounting for weight-adjusted drug doses. Instead, HbA1c reductions were comparable between men and women (mean difference 0.4 mmol/mol; p = 0.21).In conclusion, in this real-world cohort, women achieved greater weight loss than men after GLP-1RA initiation, independently of dosing. These findings highlight sex as a potential predictor of GLP-1RA response and support individualized T2D management. Further investigation is needed to clarify the biological mechanisms underlying this sex-specific response.